Transformations in cryovacuum condensates of ethanol comparison with bulk samples - Sokolov, D.; Kurnosov, V.; Katpaeva, K. (Recent Contributions to Physics, 2014)
One of the interesting properties of ethanol is its polymorphism, representing different solid phases below the melting point of159K: structural(amorphous) glass obtained by quenching over the cooled liquid below the glass transition temperature g =97K;plastic crystal, which moves to the orientationally disordered crystals upon cooling belowTg =97K;ordered(monoclinic) crystal. This paper presents the IR spectra of differentstructural andphase statesof ethanol atthe appropriate temperatureranges.